2010
DOI: 10.1051/apido/20010023
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation inMeliponaspecies (Hymenoptera: Apidae) and sub-grouping by their DNA content

Abstract: The stingless bees of the genus Melipona comprise a group with approximately 40 Neotropical species. Despite their ecological and economic importance, the size of the genomes of these species remains poorly known. Thus, the present study measured the DNA content of 15 Melipona species. The mean genome size (1C) of the females ranged from 0.27 pg to 1.38 pg, with increments of, approximately, 0.12 pg. It was possible to recognize two groups of species: the first presented relatively low DNA content (average = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The differences in the heterochromatin amounts and distribution are remarkable aspects of Melipona , and based in these differences, Rocha and Pompolo (1998) divided the genus into two groups (see introduction). Species with high heterochromatic contents also display larger genome sizes, such as M. scutellaris , whose genome is 1.08 pg (Tavares et al 2010). The notion of the amplification of repetitive DNAs, which is associated with large heterochromatic blocks, is reinforced in this work by the analysis of the DOP-PCR and C 0 t -DNA fraction probe hybridization that labeled the same regions corresponding to heterochromatin (Figure 2b, c).…”
Section: Resultsmentioning
confidence: 58%
“…The differences in the heterochromatin amounts and distribution are remarkable aspects of Melipona , and based in these differences, Rocha and Pompolo (1998) divided the genus into two groups (see introduction). Species with high heterochromatic contents also display larger genome sizes, such as M. scutellaris , whose genome is 1.08 pg (Tavares et al 2010). The notion of the amplification of repetitive DNAs, which is associated with large heterochromatic blocks, is reinforced in this work by the analysis of the DOP-PCR and C 0 t -DNA fraction probe hybridization that labeled the same regions corresponding to heterochromatin (Figure 2b, c).…”
Section: Resultsmentioning
confidence: 58%
“…Most of the estimates of genome size available for formicides have been obtained using Drosophila melanogaster as the internal standard [ 6 , 34 ], although Cardoso et al [ 14 ] also used females of Scaptotrigona xantotricha to analyze hymenopterans, in particular, stingless bees [ 35 37 ]. In the present study, D .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, only Lopes et al [37] and Tavares et al [35,36] have estimated the genome size of Scapitotrigona xantotricha, and found a difference in the values recorded for males and females. This is probably because bees, like ants, have a haplodiploid sex determination system, with haploid males and diploid females (workers and queens).…”
Section: Internal Standards Lysis Buffers and Tissuementioning
confidence: 95%
See 2 more Smart Citations